Meigs family papers - Meigs, Return Jonathan, 1740-1823.; Meigs, Return Jonathan, 1764-1825.; Meigs, Return J. (Return Jonathan), 1801-1891.
Chiefly correspondence of Return Jonathan Meigs (1740-1823) relating principally to his activities as Indian agent to the Cherokees (1801-1823), with a few letters (1772-1774) concerning his Revolutionary War service. Includes a letter (1804 Dec. 10) from Meigs to Andrew Pickens relating to Cherokee lands. Papers of Meigs's son, Return Jonathan Meigs (1764-1825), relate to his tenure as governor of Ohio (1810-1814) and include a letterbook (1820-1821) while he served as U.S. Postmaster General. Papers of Return Jonathan Meigs (1801-1891), lawyer and attorney general of Tennessee, concern the removal of Indians from Alabama and the Mississippi Territory from 1831 to 1834.
Microfilm edition available
Microfilm edition excludes the letter from Return Jonathan Meigs (1740-1823) to Andrew Pickens.
Microfilm produced from originals in the Manuscript Division.
Collection material in English.
Keywords: Pickens, Andrew, -- 1739-1817 -- Correspondence; Meigs family; United States. -- Postmaster General; Cherokee Indians; Indians of North America -- Alabama; Indians of North America -- Mississippi; Practice of law -- Tennessee; Ohio -- Politics and government; United States -- History -- Revolution, 1775-1783.; Attorneys general -- Tennessee; Cabinet officers; Governors -- Ohio; Indian agents; Lawyers